Rate of missed oesophageal cancer at routine endoscopy and survival outcomes: A multicentric cohort study. Issue 2 (March 2019) - Rodríguez de Santiago, Enrique; Hernanz, Nerea; Marcos-Prieto, Héctor Miguel; De-Jorge-Turrión, Miguel Ángel; Barreiro-Alonso, Eva; Rodríguez-Escaja, Carlos; Jiménez-Jurado, Andrea; Sierra-Morales, María; Pérez-Valle, Isabel; Machado-Volpato, Nadja; García-Prada, María; Núñez-Gómez, Laura; et al.
Background: Missed oesophageal cancer (MEC) at upper gastrointestinal endoscopy (UGE) is poorly documented. Objective: The objectives of this study were: (1) to assess the rate, predictors and survival of MEC; (2) to compare MEC and non-MEC tumours. Methods: This was a retrospective cohort study conducted at four tertiary centres. Oesophageal cancers (ECs) diagnosed between 2008 and 2015 were included. Patients with a premalignant condition (Barrett, achalasia), prior diagnosis of EC or oesophagogastric junction tumour of gastric origin were excluded. MEC was defined as EC detected within 36 months after negative UGE. Results: 123, 395 UGEs were performed during the study period, with 502 ECs being diagnosed (0.4%). A total of 391 ECs were finally included. Overall MEC rate was 6.4% (95% confidence intervals (CI): 4.4–9.3%). The interval between negative and diagnostic UGE was less than 2 years in 84% of the cases. Multivariate analysis showed that a negative endoscopy was associated with proton pump inhibitor (PPI) therapy and less experienced endoscopists. MEC was smaller than non-MEC at diagnosis (25 versus 40 mm, p = 0.021), more often flat or depressed ( p = 0.013) and less frequently diagnosed as metastatic disease ( p = 0.013). Overall 2-year survival rate was similar for MEC (20%) and non-MEC (24.1%) ( p = 0.95). Conclusions: MEC accounted for 6.4% of all ECs and was associated with poor survival. High-quality UGE and awareness of MEC may help to reduce its incidence.